Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.ebiom.2020.102777
|View full text |Cite
|
Sign up to set email alerts
|

Improving B-mode ultrasound diagnostic performance for focal liver lesions using deep learning: A multicentre study

Abstract: Background: The diagnosis performance of B-mode ultrasound (US) for focal liver lesions (FLLs) is relatively limited. We aimed to develop a deep convolutional neural network of US (DCNN-US) for aiding radiologists in classification of malignant from benign FLLs. Materials and methods: This study was conducted in 13 hospitals and finally 2143 patients with 24,343 US images were enrolled. Patients who had non-cystic FLLs with pathological results were enrolled. The FLLs from 11 hospitals were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 21 publications
0
60
1
1
Order By: Relevance
“…Two experienced radiologists reviewed all US images, who were not participated in the image acquisition and blinded to clinical information and final diagnoses of each patient. The review for US features was in concordance with a prior study (14). In brief, echogenicity was defined as mixed, hypoechoic or hyperechoic when comparing with the echogenicity of surrounding parenchyma.…”
Section: Interpretation Of Us and Cemri Featuresmentioning
confidence: 75%
See 2 more Smart Citations
“…Two experienced radiologists reviewed all US images, who were not participated in the image acquisition and blinded to clinical information and final diagnoses of each patient. The review for US features was in concordance with a prior study (14). In brief, echogenicity was defined as mixed, hypoechoic or hyperechoic when comparing with the echogenicity of surrounding parenchyma.…”
Section: Interpretation Of Us and Cemri Featuresmentioning
confidence: 75%
“…The biggest challenge in traditional machine learning and texture analysis is operator-dependently predefining region-of-interest (ROI), which could be overcome by free-hand data mining and navigating system of DLM ( 23 ). Previous literatures reported great potential of deep-learning information in differentiating FLLs based on CECT ( 24 ), CEMRI ( 25 ) and US modality ( 14 ). However, prior research groups failed to especially focus on the role of DLM in cirrhotic patients, who may have different liver cancer dynamics from normal ones ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study analyzed US images of 668 patients with primary liver cancer, consisting of 531 HCC patients, 48 cHCC-CC patients, and 89 CC patients, and found that the overall performance of the radiomics model in identifying different histopathological types of primary liver cancer yielded AUCs of 0.854 (training cohort) and 0.775 (test cohort) in the HCC vs. non-HCC radiomics model, and 0.920 (training cohort) and 0.728 (test cohort) in the CC vs. cHCC-CC radiomics model [ 79 ]. Furthermore, a multicenter study performed in 13 hospitals, including 2143 patients (24343 sonograms), has shown that deep convolutional neural network of US may have the potential to assist less experienced radiologists in improving their performance and lowering their dependence on sectional imaging in liver cancer diagnosis [ 47 ].…”
Section: Radiomics-based Us For the Diagnosis Of Hccmentioning
confidence: 99%
“…In this article of EBioMedicine, Yang and colleagues report the excellent diagnostic performance of the developed deep convolutional neural network of US (DCNN-US) in classification of malignant from benign FLLs using 11 standard still US images and clinical-ultrasonic factors [5]. It is noteworthy that DCNN-US showed higher diagnostic performance compared to experienced radiologists and comparable diagnostic performance to contrast-enhanced CT for lesions detected by US in a large external validation cohort obtained from a prospective multicentre study.…”
mentioning
confidence: 99%